Standardization Recipes of Meat Rendang With Additional Potatoes in Batipuh, Tanah Datar District - Nismar Amini; Wirnelis Syarif (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
This research aims to obtain standard recipe for beef rendang with addition potatoes. The type of research used in this research is a mixed method of qualitative and quantitative research.The research was carried out in Batipuh, tanah datar district in october 2o2o. The data sources obtained qualitative research were experts analyzing rendang, the data source for quantitative research obtained from organoIeptic test. Qualitative data collection includes observation, interviews, documentation. Quantitative data collection techniques used organoIeptic test questionnaire.Qualitative data analysis use 3 activity elements:data reduction, data presentation, drawing conclusions and quantitative data analysis techniques using the formula(Mx=Σx/N). Qualitative data validity testing participation extension, diligent observation, and tringuIation. Based on the research results, the recipe for beef rendang with addition potatoes includes number of ingredients used, the method of manufacture,and quality of beef rendang with addition of potatoes. From recipe obtained, organoIeptic test will carried out on quality to obtain quality results the Meat Rendang with Added Potatoes that have been converted. Standardization of the Recipe for Meat Rendang with Additional Potatoes, organoIeptic test was carried out to obtain the quality the Meat Rendang with Addition Potatoes, including the shape of the meat(square), color(blackish brown), aroma(fragrant), texture(soft), taste(savory) and potato(absorbed spices)